Protection of critical infrastructure and disaster risk reduction – Civil protection activities in the context of national security - Trut, Damir; Klanac, Marijana; Štajduhar, Dražen (Crisis Management Days, 2025)
The protection of critical infrastructure in the context of national security represents a key segment of the state’s strategic security management. Critical infrastructure encompasses all essential and vital sectors that enable the normal functioning of society and the economy. In today’s globalized and highly interconnected world, securing these facilities, systems, and networks is not only a technical challenge but also a strategic imperative. Disaster risk reduction in the context of national security constitutes a crucial component of a state’s policy for protecting its territory and population from natural and human-induced threats. Disasters, whether caused by natural or anthropogenic factors, can have a severe impact on national stability, the economy, infrastructure, and social cohesion. Given the increasing frequency, intensity, and diversity of extreme events, disaster risk reduction has become a priority for the sustainability of every country and the international community as a whole. Disaster risk reduction relies on the actions of every individual, from each citizen to the highest levels of state authority. Therefore, through civil protection activities, efforts are focused on developing and strengthening cooperation among all stakeholders at the local, regional, and national levels in order to ensure the most effective response to the challenges that the future may bring.